Experimental and Numerical Assessment of the Seismic Behavior of Non-uniform Slit Dampers and Bar Dampers in Moment Resisting Reinforced Concrete Frames - Rahimi, Hemat; Esfandari, Javad; TahamouliRoudsari, Mehrzad (Periodica Polytechnica Civil Engineering, 2024)
The use of lateral bearing systems to rehabilitate reinforced concrete frames has been one of the most important research topics in structural engineering. Non-uniform Slit Dampers (NSD), as well as Bar dampers, are two types of novel yielding dampers whose effects on reinforced concrete structures have been evaluated in this research. In this research, three experimental samples with a one-third scale were constructed to assess the effect of the presence of NSD and Bar damper in reinforced concrete frames. Also, 16 numerical models were created to evaluate the number of used dampers in experimental specimens in order to determine the optimal mode of using these dampers. Seismic parameters of stiffness, ultimate strength, ductility, and energy dissipation capacity were investigated in this research. The research results showed that the use of lateral bearing systems with NSD and bar dampers can have a significant impact on the seismic performance of reinforced concrete moment resisting frames. Also, in the numerical models that were made using ABAQUS software, it was concluded that the use of a smaller number of dampers compared to the experimental models can still improve the seismic parameters of the system while the cyclic capacity of the system does not drop.